Menggali Peran Suami dalam Mendukung Ibu Hamil Mengonsumsi Tablet Fe Demi Cegah Anemia - Diana Putri (Jurnal Siti Rufaidah, 2023)
This study aims to explore the experience of pregnant women in consuming Fe tablets and the role of husband support in the prevention of anemia in Bukittinggi City. The problem faced is the high rate of anemia in pregnant women in this region, which is caused by the low compliance of mothers in taking Fe tablets regularly. With a qualitative approach, in-depth interviews were conducted with pregnant women undergoing the Fe tablet supplement program to understand how their husband's support affected their compliance. The results showed that husband support had an important role in improving pregnant women's compliance, especially through emotional support, reminders, and encouragement in overcoming side effects that mothers often experience during Fe tablet consumption. Husband's support plays a significant role in maintaining the consistency of pregnant women in consuming Fe tablets, which has a positive impact on efforts to prevent anemia. The existence of a husband as a companion provides additional motivation for mothers to be disciplined in undergoing this health program. To increase the effectiveness of the anemia prevention program, it is recommended that health workers involve their husbands in health education for pregnant women regarding the importance of consuming Fe tablets. Maternal and child health programs should include a family approach, especially by increasing husbands' participation in pregnancy classes and counseling sessions, so that support for pregnant women can be maximized.